2011
DOI: 10.5194/angeo-29-1455-2011
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary coronal mass ejections in the near-Earth solar wind during the minimum periods following solar cycles 22 and 23

Abstract: Abstract. In this paper we examine the occurrence rates and properties of interplanetary coronal mass ejections (ICMEs) and solar activity levels during the minima following solar cycle 22 (January 1995-December 1997) and 23 (January 2007-April 2010) minima using observations from the OMNI data base. Throughout the minimum following cycle 22 the CME and ICME rates roughly tracked each other, while for the minimum following cycle 23 they diverged. During the minimum after solar cycle 23, there were large variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…We also demonstrated that there was a significant reduction in the Alfvénicity during these years. This clear drop in the amount of fast wind is related to the changes in the coronal global magnetic field structure [ Kilpua et al , ]. At these years, the coronal streamer belt neutral line was flat and confined close to the ecliptic and thus it was mostly the slow solar wind from the streamer belt region or coronal hole boundaries that reached the ecliptic.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that there was a significant reduction in the Alfvénicity during these years. This clear drop in the amount of fast wind is related to the changes in the coronal global magnetic field structure [ Kilpua et al , ]. At these years, the coronal streamer belt neutral line was flat and confined close to the ecliptic and thus it was mostly the slow solar wind from the streamer belt region or coronal hole boundaries that reached the ecliptic.…”
Section: Discussionmentioning
confidence: 99%
“…The MO starts at 07:00 UT and lasts until 19:11 UT. In the case of 2010 January 1 shown in Figure 5 (Kilpua et al 2011), the EPP analysis provides some clue for defining the ICME extent. At the ICME start on 22:04 UT, the EPP is zero during the first half of the MO obstacle but some electron bidirectionality is observed in the second half.…”
Section: In Situ Flux-rope Observationsmentioning
confidence: 99%
“…The diameter of the MC at 1 AU was about 0.12 AU, calculated by multiplying the duration of the MC with its average speed. The obtained width is slightly smaller than the typical MC dimension at 1 AU at solar minimum between cycles 23 and 24 of about 0.25 AU at the orbit of the Earth (Kilpua et al, 2011). The rear end of the MC was observed by Wind at about 03:45 UT when the temperature increased to 2.6 × 10 5 K, the magnetic field decreased from 11 nT to 6.5 nT and the solar wind speed increased to 500 km s −1 .…”
Section: Event Overviewmentioning
confidence: 54%